Microbial Colonization and Antibiotic Resistance Profiles in Chronic Wounds: A Comparative Study of Hidradenitis Suppurativa and Venous Ulcers - Florica Sandru; Elena Poenaru; Smaranda Stoleru; Andreea-Maria Radu; Alexandra-Maria Roman; Corina Ionescu; Aurelian Zugravu; Jafal Mugurel Nader; Livia-Cristiana Băicoianu-Nițescu (Antibiotics)
Background/Objectives: Chronic wounds, including hidradenitis suppurativa (HS) and venous ulcers (VU), are commonly associated with complex microbial communities that may influence wound healing and treatment outcomes. Understanding microbial diversity and antibiotic resistance patterns is essential in order to optimize therapeutic strategies. This study aimed to investigate the microbial populations and antibiotic resistance profiles in HS and VU patients, comparing the prevalence of common pathogens and their antimicrobial resistance profiles. Methods: We conducted a cross-sectional analysis that included a total of 112 individuals (24 with the diagnosis of hidradenitis suppurativa and 88 diagnosed with venous ulcer). Wound swabs were cultured to identify bacterial species, and antibiotic resistance was assessed using a standard panel of antibiotics. Prevalence rates of key pathogens, such as Staphylococcus aureus, Pseudomonas aeruginosa, and Enterococcus faecalis, were compared between the two groups. Resistance patterns were analyzed using statistical methods to identify significant differences. Results: Staphylococcus aureus was the most common pathogen in both groups (45.8% in HS; 38.6% in VU), with a notable prevalence of methicillin-resistant S. aureus (MRSA). Pseudomonas aeruginosa was exclusively identified in VU patients (27.3%), while beta-hemolytic Streptococcus and Corynebacterium amycolatum were identified in HS cases only. Antibiotic resistance was moderate, notably in S. aureus and Proteus mirabilis, while one case of multidrug-resistant Pseudomonas aeruginosa was identified. Conclusions: This study highlights the distinctive microbial profiles and antibiotic resistance patterns in HS and VU chronic wounds. The predominance of S. aureus in both groups underscores the need for targeted therapies, while the absence of P. aeruginosa in HS wounds and the higher prevalence of other species emphasizes wound-specific microbial variations. These findings underscore the importance of personalized treatment strategies and continuous surveillance of antimicrobial resistance.